Exercise as a substitute for traditional airway clearance in cystic fibrosis: a systematic review. Issue 8 (22nd December 2020) - Ward, Nathan; Morrow, Scott; Stiller, Kathy; Holland, Anne E
Abstract : Background: Exercise and traditional airway clearance techniques (ACTs) are both routinely recommended for people with cystic fibrosis (CF), with some people using exercise as a substitute for traditional ACTs. The effectiveness of this is unclear. We systematically reviewed the evidence for using exercise as a substitute for traditional ACTs in people with CF. Methods: A systematic database and literature search were undertaken of studies comparing exercise to rest or traditional ACTs. Primary outcomes were respiratory function, respiratory exacerbations and health-related quality of life. Secondary outcomes included mucociliary clearance (MCC), sputum weight and ease of expectoration. Data are mean difference (95% CI). Results: A total of 12 studies (15 reports) were included, all of short duration (single session to 2 weeks). In crossover trials, exercise did not improve forced expiratory volume in one second in comparison to rest, but peak expiratory flow was increased during treadmill exercise (mean difference (MD) range 1.00–1.16 L/s) and cycle ergometry (1.19 (0.96 to 1.42) L/s). Treadmill exercise improved MCC (2.6 (1.6 to 3.6)%) and ease of expectoration (MD range 1.3–1.8 cm) compared with rest. No consistent differences in respiratory function were evident when exercise was compared with traditional ACTs (four crossover studies). There was no significant difference in MCC or sputum weight in studies where forced expirations were included in the exercise intervention. Conclusions: Exercise improves ease of expectoration and sputum clearance compared with rest. Exercise, incorporating forced expirations, may have similar effects to traditional ACTs over the short term. There are no data comparing exercise to traditional ACTs over the longer term. PROSPERO registration number: CRD42018102780.